Cure, Poison or Placebo? The Consequences of Populist and Radical Party Success for Representative Democracy - Heiko Giebler; Annika Werner (Representation, 2020)
The spread and success of radical and populist parties has triggered a profound debate on the state of democracy. Not only are these parties described as the outcome of a democratic malaise in which democratic regimes had ceased to integrate, represent and engage all their citizens. At the same time, questions arose as to the consequences of these parties for existing representative democracies. Could radical and populist parties be a (partial) cure to the woes of established democracies? Or would they make the democratic malaise even worse, further poisoning an already sick patient? Could it be that these parties act like a placebo that exists because of the democratic malaise but does not actually change anything except for those who desperately want to believe in an effect? The contributions to this Special Issue address questions of the impact of radical and populist parties on representative democracy. This introduction systematise their findings along party functions and draws broader conclusions.
Keywords: 300; populist parties; radical parties; representative democracy; party functions